Tissue Modification in Nonsurgical Facelift Options - Harrison, Lucas M.; Shapiro, Ryan; Johnson, R Michael (Facial Plastic Surgery, 2020)
Nonsurgical facelifts are a term for a heterogeneous group of procedures used by physicians to improve facial rejuvenation without the use of operative techniques. Patients demand these services due to the reduced recovery time and generally lower risk. However, nonsurgical techniques, to be effective, must induce conformational change in the cells and tissues of the face. Therefore, these techniques are significant procedures that have associated risks. Understanding the tissue modifications and mechanisms of action of these techniques is vital to their safe and effective use. The purpose of this article is to provide a background of tissue modification in nonsurgical facelift options.
Keywords: nonsurgical; facial rejuvenation; lasers; radiofrequency; neuromodulators